2020
DOI: 10.1016/j.ejvs.2019.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Regeneration of Mitochondrial Function in Gastrocnemius Muscle in Peripheral Arterial Disease After Successful Revascularisation

Abstract: WHAT THIS PAPER ADDS Affected muscle regions in peripheral arterial disease (PAD) are known to be altered by reduced blood supply. Clinical research projects predominantly deal with the investigation of the underlying atherosclerotic lesions and the development of new technical devices for the treatment of those lesions. The investigation of the lower extremity PAD end organ, namely the muscle, has been neglected so far, and in particular the effect of revascularisation on affected muscle regions has not been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 26 publications
1
22
0
Order By: Relevance
“…Patients’ characteristics including presence of cardiovascular risk factors are given in Table 1 . Detailed information about the clinical stage of PAD, morphology of SFA lesions and performed vascular interventions have been described earlier [ 10 ] and are shown in detail in Additional file 1 : Table S1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Patients’ characteristics including presence of cardiovascular risk factors are given in Table 1 . Detailed information about the clinical stage of PAD, morphology of SFA lesions and performed vascular interventions have been described earlier [ 10 ] and are shown in detail in Additional file 1 : Table S1.…”
Section: Resultsmentioning
confidence: 99%
“…With the titration of 5 mM pyruvate and 10 mM succinate, CI&II-linked respiration yields oxidative phosphorylation (OXPHOS) capacity ( P ). Stepwise addition (0.05 mM steps) of the protonophore carbonyl cyanide p-(triflouromethoxy) phenylhydrazone (FCCP) yields maximum mitochondrial respiration or electron transfer ( E ) capacity [ 10 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Following this initial publication, this same group examined a larger population (n = 25 PAD and 16 controls) and observed similar findings of decreased mitochondrial respiration, specifically supported by electron transport system complexes I, III, and IV but not II [79]. Recent studies employing a similar methodology for mitochondrial assessments have reported that age-matched control subjects and mild PAD patients with intermittent claudication have similar muscle mitochondrial respiratory function [82,83,86] or even elevated mitochondrial respiratory capacity normalized to either weight or citrate synthase activity [84]. These contrasting findings are likely explained by the clinical characteristics of patients in the studies.…”
Section: Skeletal Muscle Mitochondrial Function: Evidence From Pad Pamentioning
confidence: 61%
“…Data are presented as a percentage of the control group and patients were classified as intermittent claudicants (IC-mild PAD) or chronic limb-threatening ischemia (CLTI-severe PAD) based on the clinical characteristics provided by the authors of each paper. Please refer to the following references for these original studies:[53,[74][75][76][77][78][79][80][81][82][83][84][85][86][87].…”
mentioning
confidence: 99%